2015
DOI: 10.5367/te.2014.0398
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Non-Linear Input—Output Models for Economic Impact Analyses in Tourism and Recreation

Abstract: In tourism and recreation management it is still common practice to apply traditional input–output (IO) economic impact models, despite their well-known limitations. In this study the authors analyse the usefulness of applying a non-linear input–output (NLIO) model, in which price-induced input substitution is accounted for. For large changes in final demand, a NLIO model is more useful than a traditional IO model, leading to higher or lower impacts. For small changes in final demand input substitution is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…Because of the highly aggregated nature of national and territorial accounting data, the top-down approach cannot achieve as fine a degree of process detail as the bottom-up approach. Furthermore, any analysis based on the IO model is potentially affected by the familiar limitations of the method (Briassoulis, 1991; Dwyer et al, 2004; Klijs et al, 2015). On the other hand, since it relies on existing statistical information and standardized procedures, the IO top-down approach is transparent, easily replicable and relatively inexpensive to implement.…”
Section: Literaturementioning
confidence: 99%
“…Because of the highly aggregated nature of national and territorial accounting data, the top-down approach cannot achieve as fine a degree of process detail as the bottom-up approach. Furthermore, any analysis based on the IO model is potentially affected by the familiar limitations of the method (Briassoulis, 1991; Dwyer et al, 2004; Klijs et al, 2015). On the other hand, since it relies on existing statistical information and standardized procedures, the IO top-down approach is transparent, easily replicable and relatively inexpensive to implement.…”
Section: Literaturementioning
confidence: 99%
“…Employment-based location quotients were then used to allocate those expenditures between local and imported sources. This is important due to its addressing the substitution I-O limitations, for further information on these limitations see West and Jackson (2005), Zhao and Choi (2015) and Klijs, Peerlings, and Heijman (2015). The wine industry is not included as a separate industry in the I-O tables.…”
Section: Household Expenditurementioning
confidence: 99%
“…The NLIO model we use is described in Klijs et al (2014) and in Appendix 2. However, we make three changes to this model to include labour productivity.…”
Section: Nlio Modelmentioning
confidence: 99%
“…The ratio of output to labour remains constant, which implies constant labour productivity. Klijs et al (2014) have shown how input substitution due to an increase in final demand leading to relative price changes can be included in an IO model, creating a non-linear input-output (NLIO) model. Substitution from and to labour will automatically lead to a change in the ratio of output to labour, that is, a labour productivity increase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation